Incidence and risk factors of new clinical disorders in patients with COVID-19 hyperinflammatory syndrome - Kevin E. Duong; Justin Y. Lu; Stephen Wang; Tim Q. Duong (Scientific Reports)
Abstract This study investigated new incident clinical disorders in patients with COVID-19-related hyperinflammatory syndrome (cHIS) 3.5 years post infection. We analyzed 14,335 patients hospitalized with COVID-19 from March-2020 to July-2023. cHIS was defined based on a point system that included elevated body temperature, macrophage activation, hematological dysfunction, coagulopathy, and hepatic enzyme. Outcomes were newly diagnosed disorders of hypertension, diabetes, cardiovascular diseases, chronic kidney disease (CKD), chronic obstructive pulmonary disease (COPD), and asthma post COVID-19. Cumulative incidences and hazard ratios were computed. Compared to non-cHIS patients, cHIS patients were older, fewer female, more Blacks, higher prevalence of pre-existing comorbidities. Patients with cHIS had higher risk of developing cardiovascular disease (HR = 1.24 [1.04,1.47] p < 0.05), CKD (1.24 [1.01, 1.53] p < 0.05), and obesity (1.61 [1.31,1.98], p < 0.001) but not hypertension, diabetes, COPD, and asthma. Cumulative incidence analysis showed that patients ≥ 50 years old showed markedly higher new incidences of individual new disorders compared to patients < 50 years old. COVID-19 related hyperinflammatory syndrome confers a significantly higher risk for developing new common clinical disorders. Identifying risks for developing new clinical disorders in patients with COVID-19 related hyperinflammatory syndrome may encourage diligent follow-up of high-risk individuals.